Characterization of Iron Sand and Nickel Oxide on Crystal Structure as Microwave Absorbing Material - Diana, Linda E.; Rianna, Martha; Syahwin, Syahwin; Naibaho, Yeni P. S. (Journal of Applied Geospatial Information, 2024)
We have carried out a thorough investigation to scrutinize the characteristics of iron sand and nickel oxidizer, focusing on their crystal structure as microwave-absorbing materials. The study investigates the impact of these materials on microwave absorption characteristics and the frequency range of the resulting waves. The solid-state reaction method is used in the research methodology. The research findings indicate that the combination of iron sand and nickel oxide leads to the formation of a homogeneous substance. The X-ray diffraction pattern data reveals the presence of two single-phase materials: iron sand, which consists of hematite, and nickel oxide. The iron sand and nickel oxide materials underwent characterization using EDS, revealing a composition that closely approximated stoichiometry. A Vector Network Analyzer (VNA) test shows that the iron sand and barium hexaferrite mix may be able to effectively absorb electromagnetic waves at a radar frequency of 12 GHz, leading to a -24 decibels (dB) drop.